Hydroxyl-radical footprinting combined with molecular modeling identifies unique features of DNA conformation and nucleosome positioning. Issue 16 (17th July 2017) - Shaytan, Alexey K.; Xiao, Hua; Armeev, Grigoriy A.; Wu, Carl; Landsman, David; Panchenko, Anna R.
Abstract: Nucleosomes are the most abundant protein–DNA complexes in eukaryotes that provide compaction of genomic DNA and are implicated in regulation of transcription, DNA replication and repair. The details of DNA positioning on the nucleosome and the DNA conformation can provide key regulatory signals. Hydroxyl-radical footprinting (HRF) of protein–DNA complexes is a chemical technique that probes nucleosome organization in solution with a high precision unattainable by other methods. In this work we propose an integrative modeling method for constructing high-resolution atomistic models of nucleosomes based on HRF experiments. Our method precisely identifies DNA positioning on nucleosome by combining HRF data for both DNA strands with the pseudo-symmetry constraints. We performed high-resolution HRF for Saccharomyces cerevisiae centromeric nucleosome of unknown structure and characterized it using our integrative modeling approach. Our model provides the basis for further understanding the cooperative engagement and interplay between Cse4p protein and the A-tracts important for centromere function.